Law Enforcement on Fishery: Prohibition of Trawl Nets as an Effort to Protect Small Fisherman Fairly - Ardhiansyah, Hendra Yudha; Suhartono, Slamet; Mangesti, Yovita Arie (International Journal of Business, Law, and Education, 2024)
The sea and its resources, especially fishery resources, are a gift from God Almighty for the welfare of all Indonesian people. Based on the state's right to control the earth and the natural resources contained therein, which originates from Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, the government must regulate fishery resources for the greatest prosperity of all people. The use of fishery resources is carried out with various legal products ranging from laws, government regulations, and presidential decrees to ministerial rules. Regulations on using fishery resources include prohibiting using trawl nets to catch fish in certain waters. This prohibition aims to prevent damage to the marine environment, ensure the sustainability of fishery resources, and protect small fishermen. However, in its implementation, it is still hampered by the problem of law enforcement, which is hindered by disharmony of regulations, the availability of professional law enforcement officers, and the lack of support for facilities and infrastructure considering the vast area of law enforcement. One thing that is no less important in enforcing the law on the prohibition of the use of trawl nets is the low legal awareness of fishing communities, especially industrial fishermen who only care about themselves without paying attention to the preservation of marine ecosystems, the sustainability of fishery resources, and the protection of small fishermen or traditional fishermen.